PROBLEM AS OPPORTUNITY: METACOGNITIVE LEARNING FOR DOCTORAL STUDENTS DURING THE PANDEMIC - Chowdhury, Raqib (VNU Journal of Foreign Studies; Vol 37 No 1DO - 10.25073/2525-2445/vnufs.4654, 2021)
Our pre-pandemic hubris of touting our times as an advanced digital age has given way to misgivings and scepticism as we slowly realise the limits of technological advances and how our teaching and learning practices have not been able to completely sever from age-old traditions. With unprecedented changes triggered by the global pandemic which saw schools close and move on to online spaces within the span of a few weeks all the world over, there has been a flurry of academic research into student disengagement, better integration of technology and best practices in adaptation of teaching and learning. However, much less attention has been paid to the needs of educators themselves as learners, such as those engaged in the essentially solitary experience of doctoral studies, often characterised by writer’s block, procrastination or lack of motivation. Yet the COVID-19 scenario has opened up splendid and unprecedented opportunities for reflection into our own practices. This paper critically considers the value of metacognition and self-regulated learning which current circumstances can nurture in unique ways. Studies have shown that the use of metacognitive strategies - which help learners understand their own learning - can amount to several months of progress. Much more than just learning to learn, such strategies also activate prior knowledge and make learners become higher-order agents overlooking their own learning while also being part of it, thereby leading to independent and transferrable practice. Drawing on anecdotal case studies of the presenter’s doctoral students, the paper will offer insights into ways in which early-career researchers can become effective and self-regulated learners who can take control of their own cognitive and motivational processes in planning, monitoring and evaluating skills and practices. In particular, the paper will propose guidelines through which a “securitization” can be achieved for a “post-pandemic pedagogy” (Murphy, 2020) for doctoral studies.